2021
DOI: 10.3390/cells10071592
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Actin Cytoskeleton via Rho GTPase Signalling in Dictyostelium and Mammalian Cells: A Parallel Slalom

Abstract: Both Dictyostelium amoebae and mammalian cells are endowed with an elaborate actin cytoskeleton that enables them to perform a multitude of tasks essential for survival. Although these organisms diverged more than a billion years ago, their cells share the capability of chemotactic migration, large-scale endocytosis, binary division effected by actomyosin contraction, and various types of adhesions to other cells and to the extracellular environment. The composition and dynamics of the transient actin-based st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 367 publications
(680 reference statements)
0
21
0
Order By: Relevance
“…A hallmark of the metastatic spread of tumor cells, the mesenchymal-amoeboid transition, is accompanied by a profound loss of cell adhesion to the extracellular matrix and the disappearance of canonical focal adhesions ( Liu et al, 2015 ). Amoeboid mode of migration in Dictyostelium amoeba presents a good model for the migration of metastatic cells in humans, especially since the two organisms share the basic biophysical and regulatory mechanisms responsible for the actin-driven locomotion ( Artemenko et al, 2014 ; Filić et al, 2021 ). It may seem surprising that much more is known about the structure, assembly, regulation and function of the focal adhesion complexes in mammals than about their apparently much simpler counterparts in Dictyostelium .…”
Section: Introductionmentioning
confidence: 99%
“…A hallmark of the metastatic spread of tumor cells, the mesenchymal-amoeboid transition, is accompanied by a profound loss of cell adhesion to the extracellular matrix and the disappearance of canonical focal adhesions ( Liu et al, 2015 ). Amoeboid mode of migration in Dictyostelium amoeba presents a good model for the migration of metastatic cells in humans, especially since the two organisms share the basic biophysical and regulatory mechanisms responsible for the actin-driven locomotion ( Artemenko et al, 2014 ; Filić et al, 2021 ). It may seem surprising that much more is known about the structure, assembly, regulation and function of the focal adhesion complexes in mammals than about their apparently much simpler counterparts in Dictyostelium .…”
Section: Introductionmentioning
confidence: 99%
“…Based on these studies, we conclude a likely evolutionary origin of the specific protein found in the triple intersection in our study ( Figure 5 A). Rac1 was identified in Amoebozoa [ 70 ], and is highly conserved with 91% sequence identity to human RAC1. Direct FAK and septin homologs have been found in unicellular opisthokonts [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, as presented earlier, the actin assembly-promoting activity of GxcM also requires its Rho GEF domain, implying involvement of Rho GTPase(s) in this process. Dictyostelium cells lack canonical Cdc42 and Rho homologs but express 20 Rac proteins, some of which exhibit characteristics of Cdc42 and Rho (Filic et al, 2021). We investigated whether one or more of these Rac proteins act downstream of GxcM.…”
Section: Resultsmentioning
confidence: 99%